Manipulation Under Anesthesia With Lysis of Adhesions Is Effective in Arthrofibrosis After Sulcus-Deepening Trochleoplasty: A Prospective Study. Issue 8 (22nd August 2019) - Carstensen, S. Evan; Feeley, Scott M.; Diduch, David R.
Background: Sulcus-deepening trochleoplasty has been established as an effective treatment for patellar instability due to trochlear dysplasia. However, arthrofibrosis is a known complication following trochleoplasty, which may require manipulation under anesthesia (MUA) with or without lysis of adhesions (LOA) to increase the knee range of motion (ROM), especially flexion. Purpose: To prospectively follow patients for ROM improvements and subsequent complications after undergoing MUA with or without LOA in the setting of sulcus-deepening trochleoplasty. Study Design: Case series; Level of evidence, 4. Methods: A total of 76 knees with severe trochlear dysplasia were prospectively enrolled and underwent sulcus-deepening trochleoplasty, with a mean (±SD) follow-up of 32.5 ± 19.3 months. Concomitant procedures included medial patellofemoral ligament reconstruction, lateral retinacular release, and tibial tubercle osteotomy. Physical examination including ROM and findings of recurrent patellar instability were collected for all patients. Arthrofibrosis was defined as active and passive flexion less than 90° within 3 months of surgery combined with a plateau in progress with physical therapy. Paired-samples and independent-samples t tests were used. A P value less than .05 was considered significant. Results: A total of 62 knees met inclusion and exclusion criteria and were included in the study. Of these patients, 11 experienced arthrofibrosis as a complication and underwent MUA within 3 months of their index procedure. Of these 11 patients, 9 subsequently underwent arthroscopic LOA following MUA because acceptable ROM could not be achieved with manipulation alone. Patients with arthrofibrosis had a premanipulation mean ROM that was significantly different from those without arthrofibrosis (77.3° ±18.6° vs 133.3° ± 12.7°, respectively; P < .001). In the arthrofibrotic group, postoperative ROM increased significantly after MUA and/or LOA compared with the preoperative ROM (127.3° ± 12.5° vs 77.3° ± 18.6°, respectively; P < .001). ROM in the arthrofibrotic group after MUA/LOA was not significantly different from that in the nonarthrofibrotic group (flexion, 127.3° ± 12.5° vs 133.3° ± 12.7°, respectively; P = .156). No complications from the MUA or LOA were reported at subsequent follow-up visits. Conclusion: When indicated in the setting of severe trochlear dysplasia, sulcus-deepening trochleoplasty is a treatment for disabling recurrent patellar instability with a known complication of arthrofibrosis. Initiation of postoperative physical therapy within 3 days of surgery may reduce the incidence of arthrofibrosis. If arthrofibrosis is encountered after a sulcus-deepening trochleoplasty, MUA without LOA is not as effective as when following other procedures of the knee, whereas MUA with LOA is an effective procedure likely to result in ROM and patient outcome scores similar to those of a nonarthrofibrotic knee after the same procedure. Both MUA and LOA appear to be safe based on the limited number of patients in this study without complication.